2021
DOI: 10.1186/s13102-021-00318-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity and perceived susceptibility of COVID-19 in the UK CrossFit population

Abstract: Background Contemporary literature indicates that a higher body mass index (BMI) serves as a risk factor for metabolic disease and is also correlated with greater disease severity. Subsequently, it has been linked to increased COVID-19 severity. The purpose of the study was to investigate whether regular CrossFit™ participation was associated with lower BMI, decreased COVID-19 severity and susceptibility. Methods A cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 38 publications
(48 reference statements)
0
21
1
Order By: Relevance
“…A related conclusion was reached in the study by Redwood-Brown et al so far. They reported that athletes who were already practicing CrossFit® before had not altered their training behavior during the lockdown, a fact they attributed to the increased adherence associated with CrossFit® [ 30 ]. This is consistent with further findings suggesting that one of the most important interventions for a CrossFit® training facility should be, especially during the COVID-19 pandemic, to establish a Facebook and Instagram community for its members.…”
Section: Discussionmentioning
confidence: 99%
“…A related conclusion was reached in the study by Redwood-Brown et al so far. They reported that athletes who were already practicing CrossFit® before had not altered their training behavior during the lockdown, a fact they attributed to the increased adherence associated with CrossFit® [ 30 ]. This is consistent with further findings suggesting that one of the most important interventions for a CrossFit® training facility should be, especially during the COVID-19 pandemic, to establish a Facebook and Instagram community for its members.…”
Section: Discussionmentioning
confidence: 99%
“…Of 7676 subjects, 26.1% of them contracted COVID-19. Previously, Redwood-Brown et al [5] reported in a CrossFit population of 1806 subjects from the United Kingdom (UK) that only 15 (0.83%) subjects had tested positive for COVID-19. It is worthy of understanding that Europe and Asia countries had more restrictions on social distance during the COVID-19 pandemic than Brazil, which is the key point for diminishing the COVID-19 transmission [11].…”
Section: Discussionmentioning
confidence: 99%
“…We followed the study of Redwood-Brown et al [5] and the WHO [9] to develop the present survey. An online platform survey was created via Google Forms, and its link was shared with social media.…”
Section: Assessment and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 , 19 , 20 This reduction in physical activity due to gym closures not only facilitates sedentary behavior but also reduces social interaction which for a lot of individuals impacts mental health and well‐being, particularly as many participate to reduce their symptoms of anxiety and depression. 15 , 19 Some preliminary investigations have demonstrated that if exercise behaviors are maintained during lockdown periods, the impact on mental health is limited, 18 while others have noted a decline in mental health, suggesting that further investigation is needed. 20 However, it is evident that habitually trained individuals from community focused exercise programs are more likely to maintain exercise habits during nationally imposed lockdowns and report fewer changes to mental health as a result.…”
Section: Introductionmentioning
confidence: 99%